9 - Enjeux du conflit humains- hippopotames au lac Ezanga (Lambaréné-Gabon) - Etoughé-Efé, Jean-Emery (African Sociological Review, 2022)
In central Gabon, particularly in Southern lacks area of Lambaréné, human-wildlife cohabitation is experiencing conflict due to land use and access to natural resources. There is competition between human and wild-life for these vital needs This paper, premised on the assumption that long-term co-habituation between humans and hippos at Ezanga, is marred by conflicts of various spaces, aims to highlight some of the consequences of these conflicts. It argues that human actions on wildlife environments have contributed to the remoteness or even the disappearance of hippopotamus from the mouth of Ezanga Lake which is a space where, through their movements, these mammals dredged the navigation corridors, preserving their depths. The induced disturbances result in difficulties for the residents to move§ motorized pirogue between Lambaréné and Ezanga Lake. The populations thus penalized are forced to adopt navigation strategies to compensate for the siltation, by using secondary bypass routes and thus escape the quagmire of the mouth.